Kajian Rancangan Rumah Murah Berbasis Biaya Konstruksi Sebagai Upaya Pemenuhan Kebutuhan Perumahan Bagi Masyarakat Menengah Ke Bawah (Rancang Bangun Rumah Pabrikan Dan Rumah Konvensional) - Wasino Wasino; Suwarto Suwarto; Triwardaya Triwardaya (Wahana Teknik Sipil: Jurnal Pengembangan Teknik Sipil, 2017)
The needs of homes in Indonesia currently reach 6.5 million per year, the situation is of course not easily met by the developers for various reasons, ranging from purchasing power, and expensive building materials that impact on the concept of the house offered, which is simple, healthy and cheap. To achieve these criteria, it is necessary to innovate house planning in order to obtain competitive price, so that mthe price is affordable for lower middle class people. Currently Manufacturers offer the concept of home solutions in question, through the program "Home Manufacturing", the concept needs further study. The purpose of this study is to: a) determine the dimensions of the model house, both the design of "Manufacturing House" and the conventional system, b) create architectural design for both home systems and make the home of the manufacturer home, d) financial analysis of the manufacturer's home system. The virtue of this study is to provide an overview to the public, that the concept of cheap homes ranging from construction costs and maintenance costs to the age of 20 years. The method of this research is starting from the design of the house with the type of area of 15 m2, making the model house / model, the analysis includes the budget cost plan, and financial analysis, with net present value (NPV) parameter, benefit cost ratio (BCR) and internal rate of return (IRR). The results showed that for a period of 10 years obtained Net Present Value (NPV) Rp. (- 33.640.553) <0, the value of BCR = 0, 837, <1, with the value of construction "factory house" is not financially feasible period of 10 years, while for a period of 15 years obtained Net Present Value (NPV) Rp. 32.783.131> 0, the value of BCR = 1.120. > 1, IRR = 23.22%> 11% and 20 years obtained Net Present Value (NPV) Rp 32.759.710> 0, BCR value = 1.079. > 1, IRR = 25.38%> 11%, which means that the construction of "manufacturing house" is financially feasible for a period of 15 years and 20 years, because it can provide an advantage over invested investment. From the results of the research there needs to be further research with a review of two-story househouses that utilize the beams from the "manufacturer house".Kata kunci : Rumah pabrikan, konvensional, sederhana, sehat, ekonomis